REFORMULASI SANKSI PIDANA DISKRIMINASI RAS DAN ETNIS DI INDONESIA - Irfan Ariski; Syaifullah Yophi; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Law Number 40 of 2008 concerning the Elimination of Racial and EthnicDiscrimination, actually the law against acts of racial and ethnic discrimination can preventand accommodate a person. In practice, cases of racial and ethnic discrimination haveincreased every year. In data taken from the National Commission on Human Rights (KomnasHAM), there were at least 188 complaints. Where in 2021 there were 44 complaints.Therefore, as an effort to tackle increasing racial and ethnic discrimination, and reflecting onthe Albanian state and the importance of creating a new paradigm, it is necessary toreformulate criminal sanctions as stipulated in Article 16 of Law Number 40 of 2008concerning Elimination of Racial and Ethnic Discrimination to present laws that are moreappropriate in responding to the needs of modernization. The purpose of this research was tofind out the arrangement and application of racial and ethnic discrimination criminalsanctions in the Indonesian legal system, as well as to form the idea of reformulation ofappropriate sanctions against racial and ethnic discrimination crimes in Indonesia..This research is normative legal research supported by secondary data, carried out bymaking library materials the main focus. Also called doctrinal legal research, namely legalresearch that uses data based on library research by taking quotes from reading books, orsupporting books that have something to do with the problem to be studied. Thus, this studyuses secondary data sources consisting of primary, secondary, and tertiary legal materials.This study also uses qualitative data analysis and produces descriptive data.From the results of the discussions and research conducted, several conclusions wereobtained, namely: First, the provisions and sanctions for criminal discrimination asstipulated in Article 16 of Law Number 40 of 2008 concerning the Elimination of Racial andEthnic Discrimination are no longer implemented and do not consider the impact ofpsychological violence that can be worse than physical violence and is still very weak whencompared to other countries such as the Republic of Albania and the United States. In theend, the existing sanctions become an obstacle in projecting law as a social engineering toolthat is just and beneficial to society. In practice, this has created a gap between das sollenand das sein in the application of racial and ethnic discrimination criminal sanctions inIndonesia. Second, the reformulation of criminal sanctions in the form of limiting sanctionsand adding criminal sanctions to imprisonment and fines, as well as the existence oftreatment and/or treatment in the form of rehabilitation is an idea that was prepared bytaking into account the outlook on life, awareness and legal ideals, as well as the philosophyof the Indonesian nation which originates from Pancasila and Preamble to the 1945Constitution of the Republic of Indonesia.Keywords: Ideas - Criminal Sanctions – Racial and ethnic discrimination